NILAI TOTAL PLATE COUNT (TPC) BUBUR BAYI HOME INDUSTRY - Sumantri, Janan Salma Nabilah; Safari, Wulan Fitriani; ., Septiani (Pattimura University, 2024)
Complementary foods can be divided into two groups based on how they are made, namely instant and processed complementary foods. Instant complementary foods are products that are mass-produced and packaged by factories, such as instant baby porridge, and processed complementary foods are types of complementary foods that are prepared by mothers themselves at home with various creations and variations. Total plate count (TPC) is one of the parameters of microbial contamination in food. The aim of the study was to determine the total plate count value of home industry baby porridge samples (processed complementary food) in order to ensure the safety of consumption. This study was an analytical observational study. The TPC value was determined by counting the number of bacterial colonies that grew on PCA media with dilutions of 10-1 to 10-5. The collected data were tabulated and compared with the SNI 01-7111.4-2005 standard. The results of the study obtained the average TPC values as follows: sample A (1.15 × 104 colonies/gram); sample B (1.25 × 104 colonies/gram); sample C (2.32 × 104 colonies/gram); sample D (1.84 × 104 colonies/gram) and sample E (7.95 × 103 colonies/gram). It was concluded that all baby porridge samples tested had TPC values that exceeded the threshold set by SNI 01-7111.4-2005, which is 1×102 colonies/gram.